Inline skating: Does it improve the cardiovascular system of the body? - Pyle, G. (1999)
About the effects of inline skating at all and different skating techniques on the cardiovascular system of the organism. In response to the question, "Does in-line skating provide a satisfactory aerobic workout?", Hoffman et al, concluded that the answer depends on not only the technique involved, but the person as well. The double pole technique was found to be least desirable for both highly trained and relatively sedentary persons. They found that in order to obtain a good cardiovascular workout, the double pole technique requires that the individual put forth a great effort in order to obtain a comparatively small result. The conventional and V1 techniques were both found to be good aerobic workouts for average skaters. However, as the aerobic fitness of an individual increased, it was found that a skater would have to improve his/her efforts greatly in order to maintain that level of cardiovascular fitness. While high-speed training would solve this problem, the dangers involved with such an activity rendered it an undesirable way to train. Instead the authors of the study recommended that skaters perform uphill interval training if an aerobic workout was desired.